Increasing Students' Creative Thinking Through Differentiated Learning with an CRT-Integrated PjBL Model - Dian Nur Aisah; Kukuh Munandar; Gandu Wadiono; Salsta Ridlotul Jannah (Bioeduca : Journal of Biology Education, 2023)
Students’ creative thinking skills need to be continuously improved. However, the creative thinking of students at SMAN Arjasa (Arjasa Senior High School) based on the observation results is still low. This research aimed to improve students' creative thinking skills through the application of differentiated learning models of Project-Based Learning (PjBL), integrated with Culturally Responsive Teaching (CRTs). This research employed classroom action research, consisting of 2 cycles including planning, acting, observing, and reflecting. The data were analyzed using a Paired Sample t-Test to determine the differences in each cycle, and an n-gain analysis was used to determine the increase in students' creative thinking skills. The results showed that the application of differentiated learning with the PjBL integrated with CRT was able to improve students' creative thinking skills in the biology subject. Learning according to students' characteristics and cultural integration provides a more meaningful learning experience for students.